Design and implementation of video servers for VoD system. (1st January 2013) - Dhage, Sudhir N.; Meshram, B.B.
An interactive video-on-demand (VoD) system allows users to access video services, such as movies, electronic encyclopaedia, interactive games, and educational videos from video servers on a network. In this paper, we proposed greedy video placement and disk-load balancing algorithms to minimise the static and dynamic loads of disks respectively. We then investigate interval caching buffer-management scheme for the wastage of memory and proposed a new innovative buffer-management scheme called multi-merge and split to reduce the buffer wastage in the interval caching buffer-management scheme. An integer constant called block-factor is defined to be a limiting factor for the extra blocks allocated for a new stream to be grouped with the existing session. The result shows that the proposed greedy video placement algorithm along with the disk load balancing algorithm evenly distributes the loads among the disks. It also shows that the MMS buffer-management scheme reduces memory wastage as the block-factor increases.